2022
DOI: 10.7719/irj.v18i1.825
|View full text |Cite
|
Sign up to set email alerts
|

Personal Financial Management and Entrepreneurial Competencies among Selected Public School Teachers in Cebu City Division

Abstract: Public school teachers are role models who mold students into better citizens, and teachers are regarded as the epitome of education and career success. Delivering financial education will be the pinnacle of absurdity if teachers do not practice personal financial management. This study investigated public school teachers' knowledge and practice of personal financial management and entrepreneurial competencies. The study employed the descriptive-correlational method, administered to 229 selected teachers in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The researchers found that a lack of knowledge and an unrestricted revenue-generating crypto game led to high trust difficulties regarding privacy, security, design, and usability. Moreover, Polinar et al (2022) revealed in their study that selected public school teachers have poor knowledge and practice of investments implying that they are not motivated to put their money to work for them and grow rapidly over time. Table 5 summarizes the results of the Pearson correlation coefficient of the different variables of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that a lack of knowledge and an unrestricted revenue-generating crypto game led to high trust difficulties regarding privacy, security, design, and usability. Moreover, Polinar et al (2022) revealed in their study that selected public school teachers have poor knowledge and practice of investments implying that they are not motivated to put their money to work for them and grow rapidly over time. Table 5 summarizes the results of the Pearson correlation coefficient of the different variables of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The results were supported by Docena's study (2020), which asserted that respondents' capacity to manage their financial resources might be enhanced by financial literacy. A study found a strong correlation between personal financial management knowledge and practice (Polinar et al, 2022). The study reveals that the more public school teachers learn about how to implement budgeting, saving enough money, spending wisely, setting aside enough for emergencies, managing debt effectively, getting both life and nonlife insurance, allocating money for investments, and setting up retirement accounts, the more they will put that knowledge into practice and, as a result, they will develop financial confidence in dealing with monetary uncertainties.…”
Section: Resultsmentioning
confidence: 99%